Impact of Training and Practice Setting on the Physician's Opinion Regarding the Treatment of Calcium Channel Blocker Poisoning: A Survey of Emergency Physicians - Maude St-Onge; Steve Fan Chun-Po; René Blais (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2016)
Background: A study published by St-Onge at al. (2012), identified an important variation in practice in regards to the management of calcium channel blocker (CCB) poisoning. The objectives of this study was to evaluate if the opinions of emergency physicians regarding the treatment of CCB poisonings varied and are influenced by their training and practice setting. Methods: A survey was conducted among emergency physicians working in a Canadian province (September 2008 to 2011). A weight-based group sampling method was used to identify the emergency departments where clinicians were invited to participate. During one of the emergency department meetings, clinicians were asked to select their management for six diltiazem poisoning scenarios, and identified which resources were available at their hospital. Results: A total of 19 emergency departments (140 emergency physicians) participated in the study. A greater proportion of clinicians with a 5 year FRCPC(EM) certificate compared to family physicians considered the administration of high-dose insulin (Case 3: OR 9.40 95%CI 2.26 to 45.68 p=0.0047; Case 4: OR 5.97 95%CI 1.48 to 28.17 p=0.0301). There was also a trend for a greater use of calcium for one of two cases for which it was applicable (Case 4: OR 7.62 95%CI 1.15 to 153.91 p=0.0543). Only internal pacemaker, extracorporeal life support and levosimendan were significantly reported as being unavailable in community/primary centers (p0.05). Conclusion: The emergency physicians' opinion regarding the management of CCB poisoning varies and is influenced by their training. Access to resources varied mainly depending on the practice setting.